Effect of silicon dioxide nanoparticles on the flexural strength of heat-polymerized acrylic denture base material: A systematic review and meta-analysis - Ahmad M. Al-Thobity; Mohammed M. Gad (Saudi Dental Journal)
Objective: This study evaluated the influence of silicon dioxide (SiO2) nanoparticles on the flexural strength of heat-polymerized denture base materials. Background: Nanoparticles have been incorporated into the denture base materials in different proportions to enhance the mechanical properties. Recently, the incorporation of SiO2 nanoparticles at low concentrations has shown promising outcomes. Materials and Methods: Following the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) protocol, this study was designed with the following focused question: “Does the addition of SiO2 nanoparticles improve the flexural strength of heat-polymerized acrylic resins?” The inclusion criteria included in-vitro studies that assessed the flexural strength of SiO2 nanoparticle-reinforced heat-polymerized acrylic denture base resins tested according to American Dental Association specifications. The database search involved articles published from 2005 to 2020 on PubMed/MEDLINE, Web of Science, Google Scholar, and Scopus using the following keywords: SiO2, nanosilica, silica oxide, nanoparticles, denture base resin, acrylic resin, polymethyl methacrylate, PMMA, flexural strength, and mechanical properties. Results: Among 167 studies, five papers fulfilled the inclusion criteria and were added for the data analysis and meta-analysis. Proportions of incorporated SiO2 nanoparticles ranged from 0.25% to 15% and the reported flexural strength values for the reinforced acrylic resin ranged from 41.25 MPa to 124.56 MPa. The meta-analysis revealed no significant effect on the flexural strength between the unmodified and the SiO2 nanoparticle-reinforced acrylic resin. Conclusion: Therefore, No particular concentration of SiO2 nanoparticles could be recommended for heat-polymerized denture base reinforcement.